(3UahI GdePgH ef fgGjI GdeWdHs - (3GHf GHi YUQhf CHh SYO YHO Gddg Hf eMeO Hf gHg Gdgd GdeWgQ Hf Ydis; (3CHj GdeYGdj YHO Gdedc Hf YHO Gddg Hf jhSa GdLhjfj, EeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3jHOC HcdGe Ydi OHZ LdO GdTGg s
(3BNQgG (B:s
(3jfJgi HHGH fPQ GdgOi hHJeGeg jced QHY GdYHGOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
Keywords: (3CUhd Gdabgs